2003
DOI: 10.1099/jmm.0.05179-0
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in a geriatric unit: a prospective epidemiological study employing a novel S-layer typing method

Abstract: Clostridium difficile is the major identifiable cause of antibiotic-associated diarrhoea in the UK. The aim of this study was to employ traditional culture, toxin detection and a novel typing method to determine the level of C. difficile colonization and disease in a population of elderly patients and to investigate the association between strains in the patients and their environment. Three hundred and ninety patients between 62 and 101 years of age admitted to a geriatric unit in the Royal Victoria Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Strain 338a is of S-type 5236 (ribotype 1) and was present in 78 % of cases of C. difficile diarrhoea in a geriatric unit in the Royal Victoria Hospital, Edinburgh (McCoubrey et al, 2003). Strains were grown from spores stored in cooked meat broth [anaerobic investigation medium (AIM) with cooked meat particles (Brown et al, 1996)].…”
Section: Methodsmentioning
confidence: 99%
“…Strain 338a is of S-type 5236 (ribotype 1) and was present in 78 % of cases of C. difficile diarrhoea in a geriatric unit in the Royal Victoria Hospital, Edinburgh (McCoubrey et al, 2003). Strains were grown from spores stored in cooked meat broth [anaerobic investigation medium (AIM) with cooked meat particles (Brown et al, 1996)].…”
Section: Methodsmentioning
confidence: 99%
“…It has already been reported that C. difficile surface proteins display a high variability (Péchiné et al, 2005). McCoubrey et al (2003) studied the variation in the molecular mass of the C. difficile S-layer proteins and identified seven S types among 100 isolates. The C. difficile S layer is composed of two proteins of variable size: a higher-molecular-mass protein of 48-56 kDa encoded by the conserved 39-terminal part of the slpA gene and a lower-molecular-mass protein of 36-45 kDa encoded by the variable 59-terminal part of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…They described a good correlation between the two methods and proposed PCR-RFLP on the fliC gene as an additional typing method. Previous reports have also described the variability of the S-layer protein (SlpA) among C. difficile isolates (Calabi et al, 2001;Kato et al, 2005;McCoubrey et al, 2003). Karjalainen et al (2002) suggested that genotyping based on slpA gene studies could be useful for typing strains.…”
Section: Introductionmentioning
confidence: 99%
“…Stool carriage of C. difficile reaches 16%–35% in hospitalized inpatients, with percentages proportional to the duration of hospital stay and exposure to antibiotics 26, 27. CDAD is characterized by a progression from an uncolonized state to C. difficile colonization, followed by toxin production 28. This process, in part, depends on the specific strain of C. difficile, as well as the immune status of the host.…”
Section: Background and Epidemiologymentioning
confidence: 99%